2016
DOI: 10.1097/md.0000000000003028
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure Variability is a Novel Risk Factor for Rebleeding in Acute Subarachnoid Hemorrhage

Abstract: Rebleeding of an aneurysm is a major cause of morbidity and mortality after subarachnoid hemorrhage (SAH). Whereas numerous studies have demonstrated predictors of rebleeding and effect of systolic blood pressure variability (SBPV) on stroke, few data on the association between SBPV and rebleeding.Here, we sought to identify the effect of SBPV on rebleeding in acute aneurysmal SAH.Case–control study.From January 2010 to June 2015, 612 patients with aneurysmal SAH were enrolled in our tertiary care medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
0
14
1
6
Order By: Relevance
“…Despite several reports on the dismal prognosis of inhospital rebleeding [8,19,20], we found 68.2% favorable outcome (mRS=0, 1 and 2) in our series. We believe that the lobectomy with a large Frazier suction tip (Fr 12) in this technique provides the ideal surgical corridor for access to the aneurysm and its main feeders without causing significant neurologic damages (Figure 1; A, B and C).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite several reports on the dismal prognosis of inhospital rebleeding [8,19,20], we found 68.2% favorable outcome (mRS=0, 1 and 2) in our series. We believe that the lobectomy with a large Frazier suction tip (Fr 12) in this technique provides the ideal surgical corridor for access to the aneurysm and its main feeders without causing significant neurologic damages (Figure 1; A, B and C).…”
Section: Discussioncontrasting
confidence: 99%
“…With the provided technique, we have achieved favorable outcomes in as much as 68% (15 of 22) of patients. functional outcome [8,19,20]. Data regarding the efficacy of antifibrinolytics in prevention of rebleeding are equivocal [21] and early surgery still remains the only hope they have for survival.…”
Section: Plain Language Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…European guidelines recommend a MAP above 90 mmHg to maintain proper CPP [22]. Recent studies have reported that BP variability is also associated with rebleeding or other negative outcomes in patients with acute SAH [23,24]. In the case of symptomatic cerebral vasospasm and delayed cerebral ischemia after SAH, induced hypertension is recommended by some guidelines [20,21].…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%
“…Ebenso zeigte eine größere retrospektive Observations-studie (n = 612), dass spezifische Blutdruckparameter, wie z. B. die systolische Blutdruckvariabilität, mit einer erhöhten Nachblutungsrate assoziiert sind [75]. Im Umkehrschluss identifizierte eine weitere retrospektive Arbeit (n = 309), dass ein systolischer Blutdruck von um die 120 mmHg (100-140 mmHg) mit selteneren Nachblutungen vergesellschaftet sei [76].…”
Section: Merkeunclassified